Let us say we have an RxC table, when R and C are not necessarily equal, when is the maximum value of the Chi Square statistic achieved? and how can this be proven?

  • $\begingroup$ What other constraints do you want to put on this? For example, I assume you're interested in the maximum value for a certain fixed sample size. (??) $\endgroup$ – cardinal Aug 1 '11 at 17:53
  • $\begingroup$ Indeed. This is a follow-up question to enable the generalization of this: stats.stackexchange.com/questions/13211/… $\endgroup$ – Tal Galili Aug 1 '11 at 17:56
  • $\begingroup$ Hi Caracal - where might I find this proof? (thanks) $\endgroup$ – Tal Galili Aug 1 '11 at 18:05

Assume we have an $I \times J$ table of relative frequencies $f_{ij} \; (1 \leq i \leq I, 1 \leq j \leq J)$, where (without loss of generality) $I < J$:

$ \begin{array}{ccccc|l} f_{11} & \ldots & f_{1j} & \ldots & f_{1J} & f_{1.} \\ \vdots & \ddots & \vdots & \ddots & \vdots & \vdots \\ f_{i1} & \ldots & f_{ij} & \ldots & f_{iJ} & f_{i.} \\ \vdots & \ddots & \vdots & \ddots & \vdots & \vdots \\ f_{I1} & \ldots & f_{Ij} & \ldots & f_{IJ} & f_{I.} \\\hline f_{.1} & \ldots & f_{.j} & \ldots & f_{.J} & 1 \end{array} $

Now define $\varphi^{2} := \chi^{2} / N = \sum_{i}\sum_{j} \frac{(f_{ij} - e_{ij})^{2}}{e_{ij}}$ where $e_{ij} := f_{i.} f_{.j}$. The claim is that $\chi^{2} \leq N \cdot (I-1$), i.e., $\varphi^{2} \leq I-1$. For $\varphi^{2}$ to be defined, we need to assume that all $e_{ij} > 0$, i.e., all $f_{i.} > 0$ and $f_{.j} > 0$. This means that in each row, as well as in each column, at least one $f_{ij} > 0$. Now rewrite $\varphi^{2} = \left(\sum_{i}\sum_{j} \frac{f_{ij}^{2}}{e_{ij}}\right) - 1$. Adding 1, the claim can be restated as $\sum_{i}\sum_{j} \frac{f_{ij}^{2}}{e_{ij}} \leq I$. This follows because

$ \begin{array}{rcl} \sum_{i}\sum_{j} \frac{f_{ij}^{2}}{e_{ij}} &=& \sum_{i}\sum_{j} \frac{f_{ij}^{2}}{f_{i.} f_{.j}} = \sum_{i}\sum_{j} \frac{f_{ij}}{f_{i.}} \frac{f_{ij}}{f_{.j}}\\ &\leq& \sum_{i}\sum_{j} \frac{f_{ij}}{f_{i.}} = \sum_{i} \left(\frac{1}{f_{i.}} \sum_{j} f_{ij}\right)\\ &=& \sum_{i} \left(\frac{1}{f_{i.}} f_{i.}\right) = \sum_{i} 1 = I \end{array} $

The crucial step is from the first to the second line. The inequality holds because $0 \leq \frac{f_{ij}}{f_{.j}} \leq 1$ such that $\frac{f_{ij}}{f_{i.}} \frac{f_{ij}}{f_{.j}} \leq \frac{f_{ij}}{f_{i.}}$ for all $i, j$. If all elements of the sum are smaller than the corresponding elements of a second sum, then the first sum is smaller than the second one.

$\varphi^{2}$ becomes $I-1$ when $\frac{f_{ij}}{f_{i.}} \frac{f_{ij}}{f_{.j}} = \frac{f_{ij}}{f_{i.}}$ for all $i, j$. This happens when $\frac{f_{ij}}{f_{.j}} = 1$ or $\frac{f_{ij}}{f_{i.}} = 0$ for all $i, j$. This in turn happens when $f_{ij}= f_{.j}$ or $f_{ij} = 0$ for all $i, j$. This is the case under complete dependence, i.e., when in each column, only one cell has entries $> 0$.

  • $\begingroup$ Perfect, exactly what I was looking for - thank you! I was stuck in the second line when working on this myself. $\endgroup$ – Tal Galili Aug 1 '11 at 19:17

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.